(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
In this research paper, we discuss about comparison of sorting algorithms based on their performance in various scenarios and adaptability to Nigerian context. This article examines five popular sorting algorithms: bubble sort, selection sort, insertion sort, merge sort and quicksort through analysis of time complexity and space complexity. The major goal is to determine the most efficient algorithm with respect to given data sizes and conditions that are typical with computational resources available in Nigeria. It has been found out that when datasets are small, insertion sort and selection sort perform well while for larger datasets one should consider using Merge Sort or Quick Sort because they have lower time complexity O(n log n). In addition, it looks at how these algorithms manage data integrity especially in areas like financial transactions (payments) and educational data management in Nigeria. Tests were performed using integer and string datasets to investigate the practical consequences of applying these sorting algorithms in real-world Nigerian applications. The outcomes show that having an appropriate sorting technique can greatly improve the performance as well as resource utilization across many sectors thus making it one of the ways through which a country can become greater.